INNOVATION INFRASTRUCTURE AND ITS ROLE IN THE NATIONAL INNOVATION SYSTEM - Normurodov Khusan Eshmaxmatovich (Scholar Express Journal, 2023)
The article analyzed the main approaches to defining the concepts of innovation and innovation infrastructure. The subject of the study is innovation infrastructure, which is an important factor in innovation activity. The author proposed the main components of innovation activity within which there is a complex interaction of economic, social and organizational factors that determine the creation of innovations.
Keywords: innovation; economics; iinnovation infrastructure